Estudo sobre a execução da política de assistência social em municípios da região das Missões: uma análise à luz dos valores do humanismo - Rockenbach, Cleoci Werle (2017)
This research analyzes the actions developed at Social Assistance Reference Centers (CRAS) and its contribution to the formation of autonomous individuals and protagonists of their lives, and the support to the personal development of Unified Social Assistance System (SUAS) users. In view of the interest in human being enhancement as a unique and unrepeatable individual, in this study was used as theoretical reference the humanistic psychologists view about human understanding and their conception of the integral development of intrinsic potential to each person, in order to rescue the dignity of the human being. As a basis for the analysis of actions was worked on the values of the humanist culture, which rescue, highlight and praise the positive characteristics of human nature, promoting their individual and social development. As a nature of qualitative study, it is characterized as a multiple-case research, they were searched three CRAS from the missions region. For date collection was used the simple observation and the interviews with higher education professionals, who work at CRAS, composing the sample four social workers and three psychologists. The collected data analysis was performed through the content analysis technique. Based on the methods applied in this study it is possible to verify: a) with the implementation of Reference Centers in municipalities, social assistance policy has become more visible and accessible to users. b) the professionals seek to ensure access to politics as a right of users, striving to ensure the continuity of actions and understanding the preventive and protective nature of the politics; c) there are still fragmented social practices, immediatists and assistance measures; d) users are seen as individuals endowed with potentiality and capabilities who must be held accountable for their own development, improvement and provision of their self-sustaining e) the CRAS, as a basic unit of social assistance, through the work of professionals, already contributes and can contribute even more to the development of autonomous subjects and protagonists of their history, capable of transposing on their own the difficulties of their life. Based on these findings, there was a brief proposal of humanism values in the daily actions carried out at CRAS. It is hoped to contribute to the CRAS becoming a reference to stimulate the person in self-construction to excellence, thus revealing the innate talents that exist in each human being and giving back to him all his dignity. It is understood that encouraging individual development, empowering the person for the betterment of their lives, is a real and concrete possibility in social assistance policy and is also a way of building a more humane society.